Revealing dietary habits and intestinal microbiome composition of the Beijing swift (Apus apus pekinensis) through regurgitated pellets and fecal samples - Wang, Bojun; Zhang, Yaqiong; Li, Jie; Wu, Mengwei; Shi, Yingliang; Sun, Xiangnan; Xiao, Xin; Zhang, Pan; Shi, Yang; Li, Yimeng; Tian, Hengjiu (Frontiers in Microbiology, 2025)
IntroductionThe Beijing swift, an important insectivorous bird, is a key protected wild animal in Beijing. Current research on this species primarily focuses on distribution surveys and population dynamics, while systematic studies on its diet and intestinal microbiome composition remain lacking, a knowledge gap that constrains in-depth understanding of its ecological adaptability.MethodsThis study integrated DNA barcoding and high-throughput 16S rRNA gene sequencing to systematically analyze regurgitated pellets and fecal samples from ringed and rescued individuals, revealing the following findings.ResultsThe dietary composition primarily encompasses insects from five orders, Diptera, Coleoptera, Hemiptera, Hymenoptera and Lepidoptera, with significant differences observed between adults and nestlings. Dominant intestinal bacterial phyla included Proteobacteria, Firmicutes, Bacteroidota, and Actinobacteriota. Correlation network analysis indicated that Stenotrophomonas, Aminobacter, etc., exhibit extensive mutually promotive interactions with other bacteria, suggesting their potential roles as core functional bacterial communities in the intestine.DiscussionThis research provides the first evidence of dietary differentiation patterns and intestinal microbial composition characteristics of Beijing swifts, providing key foundational data for assessing its survival and adaptation mechanisms. It is highly significant for developing scientific rescue strategies and conservation initiatives.